Sphagnum fuscum Capitulum Density, Mass, and N Concentrations From N-Addition Plots in an Alberta Peatland, 2013-2015 - R Kelman Wieder; Dale H Vitt; Melanie A Vile; Jeremy A Graham; Jeremy A Hartsock; Hope Fillingim; Melissa House; James C Quinn; Kimberli D Scott; Meaghan Petix; Kelly J McMillen (Environmental Data Initiative, 2019)
Development of the oil sands has led to increasing atmospheric N deposition, with values as high as 17 kg N ha -1 yr -1 ; regional background levels <2 kg N ha -1 yr -1 . Bogs, being ombrotrophic, may be especially susceptible to increasing N deposition. To examine responses to N deposition, over five years, we experimentally applied N (as NH 4 NO 3 ) to a bog near Mariana Lakes, Alberta, at rates of 0, 5, 10, 15, 20, and 25 kg N ha -1 yr -1 , plus controls (no water or N addition). From 2013-2015, we examined the effects of N addition on changes in S. fuscum capitulum mass density, N concentrations, and N contents in plants collected in early July (summer) and early October (fall). In each year, capitulum mass density decreased with increasing N input at equal rates in summer-collected and fall-collected plants, although CMD was consistently higher in fall-collected than in summer-collected plants. For both summer- and fall-collected plants, capitulum N concentrations were unaffected by N inputs, although N concentrations were consistently higher in summer (14.4 ± 0.3 mg g -1 ) than in fall (0.7 ± 0.1 mg g -1 ). Combining CMD and capitulum N concentrations, capitulum N contents overall averaged 1.16 ± 0.04 g m -2 . Capitulum N contents decreased with increasing N input, with the response being stronger in 2013 than in 2014/2015 . These results, combined with stem and capitulum responses at Mariana Lakes Bog, suggest that increasing N loading affects not only S. fuscum NPP, but also the way in which S. fuscum grows.